1996
DOI: 10.1046/j.1365-2141.1996.d01-1851.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the leukaemic B cell in adult and childhood acute lymphoblastic leukaemia

Abstract: Immunoglobulin heavy chain gene (IgH gene) rearrangements are found in the majority of cases of B-lineage acute lymphoblastic leukaemia (ALL). We have examined bone marrow samples taken at presentation or relapse from 109 patients (79 adults and 30 children) and have performed sequence analysis of the complementarity determining region 3 (CDR3) on 65 alleles from 54 patients. We aimed to define immunoglobulin heavy chain (IgH) variable segment family use and investigate biological and structural features of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
4
16
3
Order By: Relevance
“…Resistance to chemotherapy-induced apoptosis may confer a survival advantage to a p53-mutated subclone which by clonal expansion could mediate relapse. This may be of biological importance in ALL where previous studies have demonstrated oligoclonality in 25Ð30% of cases at diagnosis (Beishuizen et al, 1991;Coyle et al, 1996). We did not find a higher incidence of p53 mutations at relapse of AML.…”
Section: Discussioncontrasting
confidence: 36%
“…Resistance to chemotherapy-induced apoptosis may confer a survival advantage to a p53-mutated subclone which by clonal expansion could mediate relapse. This may be of biological importance in ALL where previous studies have demonstrated oligoclonality in 25Ð30% of cases at diagnosis (Beishuizen et al, 1991;Coyle et al, 1996). We did not find a higher incidence of p53 mutations at relapse of AML.…”
Section: Discussioncontrasting
confidence: 36%
“…Information on 102 alleles (in adults) and 91 alleles in children had been previously reported in a preliminary study. 39 Except for V H 6, the profile appears to be similar to the germline V H (rearrangable) profile.…”
Section: H Family Usage In Adult B-lineage Allmentioning
confidence: 86%
“…For comparison, previous data on V H family usage in childhood B-lineage ALL (91 clones), 39 B-cell lymphoma (36 clones), and CLL (56 clones) have been displayed in Table 4 and Figure 2C. The childhood B-lineage ALL profile appears to be most similar to the adult pre-B ALL profile, with the exception that V H 6, though overrepresented (10 of 91; 10%), is not as greatly elevated as in the adult ALL group.…”
Section: H Family Usage In Other Lymphoid Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations